2007
DOI: 10.1002/hed.20674
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative radiotherapy and bevacizumab for angiosarcoma of the head and neck: Two case studies

Abstract: The neoadjuvant combination of bevacizumab and radiation therapy is promising and should be further studied in the setting of vascular malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 31 publications
0
75
0
2
Order By: Relevance
“…Recently, bevacizumab, a recombinant humanised antibody against vascular endothelial growth factor (VEGF), has also emerged as a promising strategy, since VEGF is overexpressed in approximately 80% of human angiosarcomas. Koontz et al [20] reported that one of two patients with nasal angiosarcomas achieved complete response when treated with bevacizumab and radiotherapy. Further studies are needed to investigate the role of chemotherapy, rIL-2 and bevacizumab for angiosarcoma of the scalp and face.…”
Section: Angiosarcoma Of the Scalp And Facementioning
confidence: 99%
“…Recently, bevacizumab, a recombinant humanised antibody against vascular endothelial growth factor (VEGF), has also emerged as a promising strategy, since VEGF is overexpressed in approximately 80% of human angiosarcomas. Koontz et al [20] reported that one of two patients with nasal angiosarcomas achieved complete response when treated with bevacizumab and radiotherapy. Further studies are needed to investigate the role of chemotherapy, rIL-2 and bevacizumab for angiosarcoma of the scalp and face.…”
Section: Angiosarcoma Of the Scalp And Facementioning
confidence: 99%
“…A phase II trial concluded that bevacizumab is an effective and well-tolerated single-agent treatment for metastatic or locally advanced angiosarcoma (20). Several case reports demonstrated that combination therapy with bevacizumab and chemotherapy or radiotherapy may improve quality of life and survival in patients with metastatic angiosarcoma (21)(22)(23)(24)(25). In addition, another VEGF inhibitor, pazopanib, may prolong the PFS of metastatic non-adipocytic soft-tissue sarcoma after previous chemotherapy (26), particularly when used as maintenance therapy for PCA (16).…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54][55] Many of these treatment modalities have severe negative side effects, particularly in children. Therefore, it would be important to develop a less invasive and more targeted therapy for lesions that are amenable to local treatment, such as cutaneous hemangioma.…”
Section: Rapamycin Delivered Systemically or Topically Reduces The mentioning
confidence: 99%